PENGARUH CITRA DAN KEAMANAN TERHADAP KEPUTUSAN PENUMPANG MENGGUNAKAN MASKAPAI SRIWIJAYA AIR DI YOGYAKARTA - Arif Fakhrudin (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2021)
The purpose of this research was to found the influence of image and security towards on decision passenger using Sriwijaya Air. This reserch was conducted to passengers Sriwijaya Air in Yogyakarta. This research was conducted based on survey research. Population of this research were all passenger Sriwijaya Air. Purposive sampling was used as a sampling method with the total sample of 100 people. Data was colleted through online questionnaire to the respondent that is passengers Sriwijaya Air about image, security and decision. Multipile regression was used as analysis technique. Result have show that security there was positive influence and significance toward decision passengers using Sriwijaya Air. While Image there was positive influence but not significance toward decision passengers using Sriwijaya Air. The variabel service, image and security able to explain decision passenger at 59,5% and th balance 40,5% is explained by other variabels that aren’t included in this research.